2019
DOI: 10.1103/physrevb.99.045301
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected high inelastic phonon transport across solid-solid interface: Modal nonequilibrium molecular dynamics simulations and Landauer analysis

Abstract: As a crucial part in thermal management, interfacial thermal transport is still not well understood. In this paper, we employ the newly developed modal nonequilibrium molecular dynamics to study the Si/Ge interfacial thermal transport and clarify several long-standing issues. We find that the few atomic layers at the interface are dominated by interfacial modes, which act as a bridge that connects the bulk Si and Ge modes. Such bridging effect boosts the inelastic transport to contribute more than 50% to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 73 publications
3
80
0
2
Order By: Relevance
“…Similarly, Feng et al used a modal decomposition technique to show that inelastic channels contribute ≈45% to h K by including the bulk regions along with the interfacial region in their calculations. Their results are shown in Figure where they calculate the spectral contributions both on the Ge and Si sides.…”
Section: Advances In Molecular Dynamics Simulations To Study Thermal mentioning
confidence: 98%
See 3 more Smart Citations
“…Similarly, Feng et al used a modal decomposition technique to show that inelastic channels contribute ≈45% to h K by including the bulk regions along with the interfacial region in their calculations. Their results are shown in Figure where they calculate the spectral contributions both on the Ge and Si sides.…”
Section: Advances In Molecular Dynamics Simulations To Study Thermal mentioning
confidence: 98%
“…In this regard, interfacial thermal transport has been mainly studied via either the equilibrium MD simulations with the Green–Kubo approach or the nonequilibrium MD simulations based on the “direct” method of applying heat baths on a computational domain and determining the temperature drop at the interface . A comprehensive review of the two methods is provided by Schelling et al Variations and modifications of these two methods have resulted in computational tools that are able to calculate the modal or the spectral decomposition of heat current across interfaces . Some of the most notable results and advances in our knowledge of interfacial transport through these methods will be discussed below, as this analysis approach represents a relatively new technique to advance our understanding of phonon thermal transport across interfaces.…”
Section: Advances In Molecular Dynamics Simulations To Study Thermal mentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the first assumption, measurements of ITC at several metal-diamond interfaces exceed the upper limits of Landauer predictions by 20% to as large as 10 times, [5][6][7] as well as simulations and calculations demonstrating the inelastic phonon scattering induced by anharmonicity in the lattice, which facilitates the interfacial transport. [8][9][10][11][12][13][14][15] Regarding the second assumption, it has been demonstrated that during many applications such as irradiation-matter interactions, phonons can be driven into strong non-equilibrium by mechanisms such as selective electron-phonon (e-p) coupling, and a simple equilibrium picture leads to misleading or wrong results. For example, in Raman spectroscopy measurement of graphene's thermal conductivity, a simple two-temperature model (TTM) assuming local thermal equilibrium will under-predict the thermal conductivity by more than 50%.…”
Section: Introductionmentioning
confidence: 99%